2022
DOI: 10.1177/03611981221088225
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Laboratory Evaluation of Recycling Agent Treated Plant-Produced Asphalt Mixtures

Abstract: Recycling agent (RA) is typically used to restore or rejuvenate the properties of aged asphalt to desired properties. This study was motivated to comprehensively characterize the performance of asphalt mixtures treated with RA. The overarching goal of the research project is to provide guidance to agencies for revising asphalt mixture specifications to include RAs. Ten plant-produced mixtures were evaluated including three control mixtures (with 30 and 40% reclaimed asphalt pavement [RAP]) and seven 40% RAP mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The use of RA in the RAP restoration process is becoming more and more frequent. However, some studies have found that although RA can improve the performance of aged asphalt, its effectiveness may decrease as the aging time increases [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The use of RA in the RAP restoration process is becoming more and more frequent. However, some studies have found that although RA can improve the performance of aged asphalt, its effectiveness may decrease as the aging time increases [17,18].…”
Section: Introductionmentioning
confidence: 99%